Two-by-two contingency tables displaying the frequency of preferred upper extremity for writing, throwing, and hand grip strength tasks (n = 34). - Mohamadreza Hatefi (17404034) (2025)
Two-by-two contingency tables displaying the frequency of preferred upper extremity for writing, throwing, and hand grip strength tasks (n = 34).